Effect of new oral anticoagulants on microcirculation in ischemic diabetic foot ulcer - Khaled Attia; Mahmoud Moawad; Walied Khereba (Al-Azhar Assiut Medical Journal, 2022)
Background and aim Diabetic patients with foot ulcer and peripheral ischemia were shown to be associated with hypercoagulation and dysfunction in the fibrinolytic system that in turn would affect the healing of the ulcer. The authors aimed to investigate the role of rivaroxaban in improving the microcirculation of the skin and peripheral tissues and how it can improve ischemic diabetic foot ulcers. Patient and methods The authors conducted an observational retrospective case–control study at Al-Azhar University Hospital, New Damietta, from January 2015 till December 2020. Diabetic patients with foot ulcer and peripheral limb ischemia who received rivaroxaban till ulcer healing were considered as the case group, whereas patients who did not receive rivaroxaban were considered as the control group. Clinical assessment and pulse oximeter were used for the assessment of transcutaneous microcirculation. Results Throughout the 5 years of the study, 172 patients were included; the case group included 87 patients and the control group included 85 patients. There was a significant difference between the two groups regarding the improvement of limb ischemia, tissue plasminogen activator antigen, and transcutaneous microcirculation (P<0.05). Before the treatment, there was a significant correlation between both permeability coefficient and plasma fibrinogen and transcutaneous microcirculation. Conclusion The oxygenation of the ulcer and the microcirculation were found to be improved in the case group and accelerate wound healing in the ischemic diabetic foot.